Resilience, Sense of Coherence, and Coping with Stress as Predictors of Psychological Well-Being in the Course of Schizophrenia. The Study Design - Izydorczyk, Bernadetta (Int J Environ Res Public Health, 2019)
The main research objective was seeking for the predictive role of such personal resources as resilience, sense of coherence, and coping with stress in psychological well-being of schizophrenia patients and their treatment. The study group comprised 201 individuals with schizophrenia, aged between 18 and 62. The following instruments were used: The sense of coherence scale SOC-29, The resilience scale for adults, polish adaptation of the stress appraisal measure, semistructured clinical interview, the positive and negative syndrome scale, the mood scale, and the general health questionnaire. A stepwise regression analysis aimed at selecting a group of significant predictors for the verified factors of psychological well-being in patients suffering from schizophrenia was carried out. The results of the study demonstrated the following to be significant predictors of psychological well-being in patients with schizophrenia: Resilience (explaining significantly the level of schizophrenic symptomatology Beta = −0.30, negative symptoms Beta = −0.385, and cognitive disorders Beta = −0.303), sense of coherence, which significantly predicted mood (in the case of manageability, Beta = 0.580 for positive mood, and Beta = 0.534 for negative mood) and psychiatric symptomatology (comprehensibility, Beta = 0.311 for negative symptoms, Beta = 0.173 for excessive arousal, and Beta = 0.330 for cognitive disorganization). The level of perceived stress appraised as challenge predicted positive mood (Beta = 0.164), while stress appraisal in terms of threat served as a predictor for negative mood and depressiveness (Beta = 0.190). The study results can prove helpful in creating therapeutic and programs and psychiatric rehabilitation for patients with schizophrenia.